THE IDEA OF HERO IN JAMES MCTEIGUS V FOR VENDETTA - Danar Pratanda Yudistira; Mamik Tri Wedawati (Universitas Negeri Surabaya, 2022)
This study will focus on supporting the main character as a hero who fights against the government. Society is pressured by many things, even though it is all about vengeance from the main character’s point of view, yet Evey (a side character) is a genius hero. This study used a theory from the Hero’s Journey by Joseph Campbell and a social representative theory whose data is taken from character dialogue through a V for Vendetta film. This study portrayed significant focuses passed on the portrayal of Evey’s character who expects somebody who moves to express the hearts of individuals to know about the thing they encounter in their lives. The focus point sought by the writer is about the hero figure and James McTeigue’s idea to describe or represent. A hero’s idea rare in figure V, which incidentally does what makes him represented as a hero figure, is to avenge. The writer uses V for Vendetta, script, and movie by James McTeigue as the data source to be analyzed. In this study, the researcher will use qualitative research in the form of literary work. The research object is the idea of the hero, reflected in James McTeigue’s V for Vendetta.